2007
DOI: 10.22495/cocv4i2c2p1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on board size and information asymmetry: A capital markets perspective

Abstract: We examine the relation of board size with market liquidity and adverse selection costs using a sample of Fortune 200 companies. After controlling for firm specifics, equity characteristics, and ratio of insiders, we find a direct relation between board size and equity market liquidity. Our findings indicate that board size is positively and significantly related to dollar depth but has no impact on bid-ask spreads. Furthermore, using the adverse selection component of the bid-ask spread as a proxy for transpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This means that the larger the size of the board, the lower the information asymmetry. This is in line with the results of [ 34 , 35 ] and is also consistent with the view that larger boards mostly have more resources to control skills and managerial performance so as to form many effectual committees, assign tasks, and allow for greater argument on corporate issues. This may lead to lower information asymmetry and greater transparency [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This means that the larger the size of the board, the lower the information asymmetry. This is in line with the results of [ 34 , 35 ] and is also consistent with the view that larger boards mostly have more resources to control skills and managerial performance so as to form many effectual committees, assign tasks, and allow for greater argument on corporate issues. This may lead to lower information asymmetry and greater transparency [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 90%
“…Larger boards are characterised by having the necessary skills to facilitate greater discussion about corporate matters, assign tasks, and form diverse effective committees [ 32 , 33 ]. In this regard, Flaherty et al [ 34 ] and Cai et al [ 35 ] found that larger boards mitigate asymmetric information as well as decreasing opacity [ 36 ]. The second stream argues that boards with more directors may possess some weaknesses that affect their performance and efficiency, such as social loafing and free riding [ 27 , 37 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of good governance in providing greater quality of information as well as a greater number of investors should therefore further enhance the level of information brought on by stock liquidity. Furthermore, the quality of governance and its attributes have been studied and found to influence the level of information asymmetry (Elbadry, Gounopoulos & Skinner 2015;Cormier et al 2010;Flaherty, Li & Small 2007). In short, governance quality has been found in past studies to have a significant effect on the level of information asymmetry, increased the number of investors' participation through greater protection, improved the quality of information delivered as well as greater transparency.…”
Section: Introductionmentioning
confidence: 99%